Pierwszy raz w zyciu - Kedzierski, Jerzy Z. (Warszawa : Krajowa Agencja Wydawnicza, 1985)
A novel in which three men tell their tale of events during WW II, in Poland. Some of the material is autobiographical.
1. Pierwszy raz w zyciu -- 2. Sportek -- 3. Charles.
Keywords: World War, 1939-1945 -- Poland -- Fiction